CONCEPTUAL TECHNO-ECONOMIC ANALYSIS OF RETROFITTING A 210 MW THERMAL HEAVY-OIL POWER PLANT WITH A MOLTEN SALT THERMAL ENERGY STORAGE SYSTEM FOR RENEWABLE POWER: A CASE ANALYSIS OF TEC NEGOTINO - Minovski, Dragan; Sterjova, Marija (Journal of Energy Technology, 2025)
This study conducts a conceptual techno-economic analysis to explore the possibility of retrofitting a 210 MW thermal heavy-oil power plant, TEC Negotino, with a molten salt thermal energy storage system (a Carnot battery). The proposed approach enables storage of surplus or curtailed renewable electricity on the grid in the form of thermal energy. This initial exploration involves analysing the sensitivity of annual energy yield, load factor, total investment cost, annual O&M cost and levelized cost of a discharging electricity with varying discharging duration, thermal storage capacity and charging duration. The results demonstrate that the most favorable annual roundtrip efficiencies and lowest levelized cost of discharge electricity were obtained for longer discharge duration (in full load hours). This approach of the possibility of repurposing TEC Negotino not only prioritizes the potential for the comprehensive decarbonization of the thermal power plant, but also conserving the majority of jobs within the power plant, making it a sustainable and economically viable initiative.